Optimizing the Performance of the Two-Wheeled Patrol Unit of the Samapta Corps to Prevent Weighted Theft Crime in the Pekalongan Police Area - Ginano, Raihan (Advances in Police Science Research Journal, 2024)
The author raises the final task with the problem of "Optimizing the Performance of the Two-wheeled Patrol Unit of the Samapta Unit to Prevent Weighted Theft Crime in the Pekalongan Police Area". Writing this final project aims to identify the two-wheeled patrol unit management system of the Pekalongan Police Samapta Unit and identify the optimization of the two-wheeled patrol unit of the Pekalongan Police Samapta Unit. This study used a qualitative approach with the type of field research by interviewing informants, observing, and studying documents. In addition, the data used was also obtained from various references such as articles, journal books and online media news that were relevant to the problem variables discussed. This study uses management theory and SWOT analysis theory as well as several concepts that are relevant to the problem, namely the patrol concept based on Perkabaharkam Number 1 of 2017 concerning Patrols, optimization concepts, weighted theft concepts, performance concepts. The two-wheeled patrol unit of the Pekalongan Police Samapta Unit is the backbone of police actions in a preemptive and preventive manner in preventing criminal acts in the jurisdiction of the Pekalongan Police, especially weighted theft. In the management system of the two-wheeled patrol unit, the Pekalongan Police Samapta Unit still found several deficiencies in terms of planning, organizing, implementation and monitoring and not in accordance with the Patrol SOP which has been regulated in Perkabaharkam Number 1 of 2017 concerning Patrol and Pekalongan Police Chief Regulation Number 22 of 2022 concerning SOP for the Implementation of the Tasks of the Pekalongan Police Samapta Unit. In addition, there were factors that influenced both internally and externally, making the implementation of two-wheeled patrols by the Pekalongan Police Samapta Unit unable to be carried out optimally. On the other hand, to optimize the implementation of two-wheeled patrols, a creative breakthrough is needed to increase the implementation of patrols.